2003
DOI: 10.1002/pon.683
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive‐existential group psychotherapy for women with primary breast cancer: A randomised controlled trial

Abstract: CEGT is a useful adjuvant psychological therapy for women with early stage breast cancer. Interaction effects between group members and therapists are relevant to outcome. Group-as-a-whole effects are powerful, but the training and experience of the therapist is especially critical to an efficacious outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
199
4
16

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(227 citation statements)
references
References 39 publications
5
199
4
16
Order By: Relevance
“…The education intervention either on its own or in combination with peer discussion generated greater benefits than supportive discussions alone. Randomized clinical trials have shown that psychosocial interventions for breast cancer patients enhance coping, social support and quality of life and reduce psychological distress (Kissane et al, 2003;Boesen et al, 2011). Besides individual psychooncological care, group psychotherapy has been described as helpful but, little research has been done (Gore-Felton et al, 2000;Neises 2008).…”
Section: Effect Of Group Therapy On Psychological Symptoms Andmentioning
confidence: 99%
“…The education intervention either on its own or in combination with peer discussion generated greater benefits than supportive discussions alone. Randomized clinical trials have shown that psychosocial interventions for breast cancer patients enhance coping, social support and quality of life and reduce psychological distress (Kissane et al, 2003;Boesen et al, 2011). Besides individual psychooncological care, group psychotherapy has been described as helpful but, little research has been done (Gore-Felton et al, 2000;Neises 2008).…”
Section: Effect Of Group Therapy On Psychological Symptoms Andmentioning
confidence: 99%
“…In all, 29 papers reporting pharmacological studies and 63 reporting psychotherapeutic interventions were identified as potentially relevant and were carefully read. Of these, we excluded 65 because they did not meet the inclusion criteria, and a further two were excluded because they were not strictly randomised controlled trials (Holland et al, 1998;Kissane et al, 2003) and one because it failed to measure baseline levels of depressive symptoms (Stiegelis et al, 2004). This left a total of 24 studies (Table 1), of which six were trials of pharmacological treatments and 18 were of psychotherapeutic interventions.…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…With a growing number of women who live with the aftermath of breast cancer for relatively long periods, it is clear that the need to understand its treatment effects and quality of life (QOL) issues becomes paramount. 21 Despite a massive amount of research on quality of life after a breast cancer diagnosis, the evidencebased knowledge gap of when, how, in what form, and what the women themselves desire to receive support about, leaves the health care professionals with very limited hands-on guidance for their everyday clinical practice. Quality of life can be studied as a multidimensional construct.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%